2013
DOI: 10.1021/la400347r
|View full text |Cite
|
Sign up to set email alerts
|

A Photoinduced Nanoparticle Separation in Microchannels via pH-Sensitive Surface Traps

Abstract: A microfluidic surface trap was developed for capturing pH-sensitive nanoparticles via a photoinitiated proton-releasing reaction of o-nitrobenzaldehyde (o-NBA) that reduces the solution pH in microchannels. The surface trap and nanoparticles were both modified with a pH-responsive polymer—poly(N-isorpopylacylamide-co-propylacrylic acid), P(NIPAAm-co-PAA). The o-NBA-coated microchannel walls demonstrated rapid proton release upon UV light irradiation, allowing the buffered solution pH in the microchannel to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…prepared a surface that showed antibacterial and antithrombotic performance by PEGylation of a quaternized chitosan (QCS) cationic surface through the benzoic imine linkage . It has been demonstrated that stimuli‐responsive surfaces can provide adaptive and specific environments for cells, thereby facilitating tissue growth and regeneration . A surface that contained benzoic imine bonds exhibited a switchable cell‐adhesion property, because the pH‐responsive window lay within the pH interval, thereby offering viability for most cell lines.…”
Section: Benzoic Imine Linkage Modesmentioning
confidence: 99%
“…prepared a surface that showed antibacterial and antithrombotic performance by PEGylation of a quaternized chitosan (QCS) cationic surface through the benzoic imine linkage . It has been demonstrated that stimuli‐responsive surfaces can provide adaptive and specific environments for cells, thereby facilitating tissue growth and regeneration . A surface that contained benzoic imine bonds exhibited a switchable cell‐adhesion property, because the pH‐responsive window lay within the pH interval, thereby offering viability for most cell lines.…”
Section: Benzoic Imine Linkage Modesmentioning
confidence: 99%
“…By Ebara et al [98] a photoinitiated proton releasing reaction of onitrobenzaldehyde (oNBA) was suggested to have (13 of 15) 1600282 wileyonlinelibrary.com pH responsive material separation. By Ebara et al [98] a photoinitiated proton releasing reaction of onitrobenzaldehyde (oNBA) was suggested to have (13 of 15) 1600282 wileyonlinelibrary.com pH responsive material separation.…”
Section: Ph Gradient In Pes Assembliesmentioning
confidence: 99%
“…NBA was integrated into polydimethylsiloxane (PDMS) microchannels by presorbing NBA within the PDMS channel surface regions [18]. NBA was dissolved in acetone and flowed into the channel for less than one minute.…”
Section: Microfluidic Devicesmentioning
confidence: 99%
“…The channels were modified with P(NIPAAm-co-PAAc) followed by coating with NBA. The suspension of beads in PBS (pH 7.4) was injected into the channel and incubated at 37 o C, and then exposed to UV lamp through a mask for one minute [18].…”
Section: A Photo-induced Gel Shrinkingmentioning
confidence: 99%
See 1 more Smart Citation